Engaging intersectionality in medical education - Eze, Princess; Forgie, Sarah; Okeke-Ihejirika, Philomina; Rashid, Marghalara (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2026)
Medical education (ME) plays a critical role in shaping future healthcare providers; however, systemic inequities persist due to biases embedded in both the formal and hidden curricula. The hidden curriculum—unspoken values, norms, and structural inequalities—reinforces implicit biases that influence professional identity formation, clinical decision-making, and patient outcomes. This theoretical paper examines how overlapping social identities can shape health experiences and access to care, and establishes a foundation for tackling systemic inequalities by advocating for the integration of an intersectional framework into ME. As healthcare institutions increasingly focus on diversity and inclusion, we aim to demonstrate that integrating intersectionality theory into ME is a timely and necessary step towards training physicians to meet the needs of diverse patient populations and reduce care disparities. We highlight how the absence of intersectional perspectives in medical training results in narrow clinical frameworks, reduced cultural competency, and the perpetuation of health disparities through the hidden curriculum. Furthermore, we outline practical strategies for embedding intersectionality into ME, such as building an intersectional curriculum, incorporating diverse case scenarios, and establishing institutional task forces. Despite potential challenges, such as resistance to change and resource constraints, implementing intersectionality in ME remains essential and can be attainable through institutional commitment and collaborative approaches. By using intersectionality as a guiding framework, ME can better prepare future healthcare providers to deliver equitable patient centered care while reducing the systemic disparities in healthcare.